Automated data collection in single particle electron microscopy - Tan, Yong Zi (Microscopy (Oxf), 2016)
Automated data collection is an integral part of modern workflows in single particle electron microscopy (EM) research. This review surveys the software packages available for automated single particle EM data collection. The degree of automation at each stage of data collection is evaluated, and the capabilities of the software packages are described. Finally, future trends in automation are discussed.